2005
DOI: 10.1016/j.chemgeo.2004.06.034
|View full text |Cite
|
Sign up to set email alerts
|

A review of the stable-isotope geochemistry of sulfate minerals in selected igneous environments and related hydrothermal systems

Abstract: The stable-isotope geochemistry of sulfate minerals that form principally in I-type igneous rocks and in the various related hydrothermal systems that develop from their magmas and evolved fluids is reviewed with respect to the degree of approach to isotope equilibrium between minerals and their parental aqueous species. Examples illustrate classical stable-isotope systematics and principles of interpretation in terms of fundamental processes that occur in these systems to produce (1) sulfate in igneous apatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
189
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(203 citation statements)
references
References 60 publications
11
189
0
3
Order By: Relevance
“…Stage 1A magmatic-hydrothermal alunite [55,56] comprises up to~300 µm long euhedral, platy crystals occurring as disseminations, as infill in vugs, and as replacements of pre-existing feldspar crystals ( Figures 4A and 5A). Stage 1B magmatic-steam alunite [55,56] occurs as coarse-grained, plumose and banded alunite in veins ( Figures 4B and 5B). Previous WDS analyses of both types of alunite showed that they belong to the alunite-natroalunite solid solution series [KAl 3 (SO 4 ) 2 (OH) 6 -NaAl 3 (SO 4 ) 2 (OH) 6 ] [30].…”
Section: Alunitementioning
confidence: 99%
“…Stage 1A magmatic-hydrothermal alunite [55,56] comprises up to~300 µm long euhedral, platy crystals occurring as disseminations, as infill in vugs, and as replacements of pre-existing feldspar crystals ( Figures 4A and 5A). Stage 1B magmatic-steam alunite [55,56] occurs as coarse-grained, plumose and banded alunite in veins ( Figures 4B and 5B). Previous WDS analyses of both types of alunite showed that they belong to the alunite-natroalunite solid solution series [KAl 3 (SO 4 ) 2 (OH) 6 -NaAl 3 (SO 4 ) 2 (OH) 6 ] [30].…”
Section: Alunitementioning
confidence: 99%
“…If a similar record were to exist on Mars, sulfur isotopic detection by the SAM QMS may detect it. Sulfur isotopic compositions of sulfate and reduced-sulfur minerals may also provide valuable information of environmental sulfur cycling by abiogenic hydrothermal (Rye, 2005;Greenwood et al, 2000) and atmospheric processes (Farquhar et al, 2000).…”
Section: Insert Figure 1 Hereaboutsmentioning
confidence: 99%
“…16 . Times required to achieve 90% equilibrium between sulfate/sulfide for pH ~4-7 and total sulfur concentration of 0.01 mol S/kg H 2 O at several temperatures are annotated across top of frame 35,36 . The shaded region shows the approximate range of  34 S observed in Gale crater samples reported here.…”
mentioning
confidence: 99%